Mapping cytoskeletal protein function in cells by means of nanobodies. Issue 10 (10th July 2013) - Van Audenhove, Isabel; Van Impe, Katrien; Ruano‐Gallego, David; De Clercq, Sarah; De Muynck, Kevin; Vanloo, Berlinda; Verstraete, Hanne; Fernández, Luis Á.; Gettemans, Jan; Ampe, Christophe; Machesky, Laura M.; Nyitrai, Miklós
<x xml:space="preserve">Abstract</x> Nanobodies or VHHs are single domain antigen binding fragments derived from heavy‐chain antibodies naturally occurring in species of the Camelidae. Due to their ease of cloning, high solubility and intrinsic stability, they can be produced at low cost. Their small size, combined with high affinity and antigen specificity, enables recognition of a broad range of structural (undruggable) proteins and enzymes alike. Focusing on two actin binding proteins, gelsolin and CapG, we summarize a general protocol for the generation, cloning and production of nanobodies. Furthermore, we describe multiple ways to characterize antigen‐nanobody binding in more detail and we shed light on some applications with recombinant nanobodies. The use of nanobodies as intrabodies is clarified through several case studies revealing new cytoskeletal protein properties and testifying to the utility of nanobodies as intracellular bona fide protein inhibitors. Moreover, as nanobodies can traverse the plasma membrane of eukaryotic cells by means of the enteropathogenic E. coli type III protein secretion system, we show that in this promising way of nanobody delivery, actin pedestal formation can be affected following nanobody injection. © 2013 Wiley Periodicals, Inc.